Alcohol use in adolescence as a risk factor for overdose in the 1986 Northern Finland Birth Cohort Study - Koivisto, Maarit K; Miettunen, Jouko; Levola, Jonna; Mustonen, Antti; Alakokkare, Anni-Emilia; Salom, Caroline L; Niemelä, Solja (European Journal of Public Health, 2022)
Peer reviewed